Analisis Pengaruh Kenaikan Tarif Cukai Hasil Tembakau Terhadap Penjualan Rokok Elektrik (Studi Kasus pada Toko KDR Vapor) - Ika Sari Apriliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Annual increases in tobacco excise rates increase state revenues, but also pose challenges for tobacco farmers and conventional and e-cigarette entrepreneurs. The impacts include increasing cigarette prices every year, which affects consumer purchasing power and business sustainability in the tobacco sector. This research aims to analyze the effect of the increase in Tobacco Products Excise rates as of January 1 2022 on sales of e-cigarettes at KDR Vapor Stores. This research is a type of descriptive research with a non-statistical quantitative approach. The data used includes changes in the selling price of e-cigarettes after the increase in Tobacco Products Excise rates, as well as sales and gross profit data for 2021 and 2022. Data collection techniques in this research are interviews and observation. The research results show that the increase in Tobacco Products Excise rates in 2022 will have a positive and significant influence on KDR Vapor Store sales. This means that the increase in excise rates on tobacco products in 2022 will increase sales at KDR Vapor stores. The increase in sales was followed by an increase in gross profit and COGS. Gross profit in 2022 will increase by IDR 914,349,630,- and COGS will increase by IDR 409,633,370,-. Gross Profit Margin Ratio percentage results for 2022, the KDR Vapor Store is considered to still be unable to run its business efficiently because the Cost of Goods Sold is relatively higher than the previous year. Suggestions for KDR Vapor Shop owners are to set competitive prices, regularly evaluate stock, and purchase products in large quantities to reduce the impact of increases in Tobacco Products Excise (CHT) rates. Expanding product variety, setting daily sales targets, and innovating with vouchers or giveaways are also important to attract and retain customers.